Daphnetin Improves Neuropathic Pain by Inhibiting the Expression of Chemokines and Inflammatory Factors in the Spinal Cord and Interfering with Glial Cell Polarization - Tianrui Zhang; Wulin Liang; Mingqian Zhang; Shuang Cui; Xiyan Huang; Wenjing Ou; Rikang Huang; Jiahui Gao; Zhanhong Jia; Shuofeng Zhang (MDPI AG, 2023)
Neuropathic pain (NP) is a common pain disease that seriously affects the quality of life and physical and mental health of patients. Daphnetin is extracted from the Daphne giraldii Nitsche and has the structure of 7,8-dihydroxy coumarin. As a natural product, daphnetin displays a wide range of pharmacological activities, such as analgesia and anti-inflammatory activities, but whether it is able to improve NP through anti-inflammatory effects is unknown. Therefore, this paper intends to investigate the mechanism of daphnetin in improving NP rats affected by the intrathecal injection of tumor necrosis factor-α (TNF-α) from the perspective of anti-inflammation. Our results showed that daphnetin significantly improved hyperalgesia in NP rats. Daphnetin inhibited the activation and polarization of glial cells and neurons in the spinal cord of NP rats and reduced the expression of mRNA and protein of inflammatory factors and chemokine pairs in the spinal cord. Daphnetin inhibited the polarization of human microglia cell 3 (HMC3) cells and human glioma cells (U251) cells toward M1 microglia and A1 astrocytes, respectively, and induced the conversion of M1 microglia and A1 astrocytes to M2 microglia and A2 astrocytes, respectively. In conclusion, daphnetin ameliorates NP by inhibiting the expression of inflammatory factors and chemokines and the polarization of glial cells in the spinal cord of NP rats. This study provides a theoretical basis for the treatment of NP with daphnetin to expand the clinical application of daphnetin.